Structural Density and Syllable Constraints in Buginese: An Analysis of Phonotactic of Sidrap Dialectal Variation - Vera Verisca; Damayanti (Yayasan Nurul Iman Muara Gading Mas, 2025)
This study investigates the phonotactic architecture of the Buginese language to determine whether syllable constraints differ significantly across word classes. The primary objective is to comparatively analyze the structural boundaries of nouns, verbs, and adjectives. Utilizing a qualitative descriptive approach supported by quantitative cross-tabulation, this research examines a corpus of ninety basic root words. Data was purposefully categorized by syntactic function, with adjectives specifically sourced from the Sidrap dialect to control for regional morphophonological variations. The findings reveal a strict tripartite typological divide, proving that phonotactic patterns are not homogeneous across the lexicon. Nouns exhibit profound diachronic stability, heavily favoring disyllabic open structures while uniquely permitting pure vowel onsets. Conversely, verbs demonstrate a dynamic, front-heavy tetrasyllabic expansion driven by prefixation and initial consonant gemination, yet they absolutely enforce an open-vowel termination. Adjectives present the highest structural density, utilizing a back-heavy architecture with complex closed codas to signal grammatical intensification. These distinct phonetic territories demonstrate that Buginese phonotactics function as active, pre-lexical syntactic markers, where the physical shape of a word categorizes its grammatical role before semantic decoding.